Culture and characterization of canine and feline corneal epithelial organoids: A new tool for the study and treatment of corneal diseases - Bedos, Leila; Wickham, Hannah; Gabriel, Vojtech; Zdyrski, Christopher; Allbaugh, Rachel A.; Sahoo, Dipak Kumar; Sebbag, Lionel; Mochel, Jonathan P.; Allenspach, Karin (Frontiers in Veterinary Science, 2022)
In this study we isolated and cultured canine and feline 3D corneal organoids. Samples derived from corneal limbal epithelium from one canine and one feline patient were obtained by enucleation after euthanasia. Stem cell isolation and organoid culture were performed by culturing organoids in Matrigel. Organoids were subsequently embedded in paraffin for further characterization. The expression of key corneal epithelial and stromal cell markers in canine and feline organoids was evaluated at the mRNA level by RNA-ISH and at the protein level by immunofluorescence (IF) and immunohistochemistry (IHC), while histochemical analysis was performed on both tissues and organoids using periodic-acid Schiff (PAS), Sirius Red, Gomori's Trichrome, and Colloidal Iron stains. IF showed consistent expression of AQP1 within canine and feline organoids and tissues. P63 was present in canine tissues, canine organoids, and feline tissues, but not in feline organoids. Results from IHC staining further confirmed the primarily epithelial origin of the organoids. Canine and feline 3D corneal organoids can successfully be cultured and maintained and express epithelial and stem cell progenitor markers typical of the cornea. This novel in vitro model can be used in veterinary ophthalmology disease modeling, corneal drug testing, and regenerative medicine.